Interactive Compromise Programming Approach for Solving Vendor Selection Problems under Fuzziness - Abd El-Wahed Khalifa, Hamiden; Goudarzi Karim, Ramin (Risk Assessment and Management Decisions, 2024)
This paper studies a Vendor Selection Problem (VSP) with fuzzy parameters in the price of a unit item, an upper limit of the quantity available, and an aggregate demand for the item. These fuzzy parameters are characterized as fuzzy numbers. An extended efficiency concept called that -efficient solution is introduced using the-level sets of fuzzy numbers. A fuzzy programming approach is applied by defining a membership function after converting the fuzzy VSP into an equivalent deterministic VSP. A linear membership function is being used to obtain optimal compromise solution. An interactive procedure for obtaining -optimal compromise solution is also presented. An illustrative numerical example is given to clarify the obtained results.